Wisata Religi Ke Makam Tokoh Islam Aceh di Peureulak: Meningkatkan Kesadaran Sejarah Pendidikan Islam Mahasiswa - Suhelayanti; Amiruddin; Nur, Muhammad (Al-Ikhtibar: Jurnal Ilmu Pendidikan, 2024)
This study aims to analyze the impact of religious tourism visits to the graves of Islamic figures in Aceh, particularly in Peureulak, on students' understanding of the history of Islamic education. The method used is qualitative with a case study approach. Data were collected through observations, in-depth interviews, and questionnaires filled out by students after the visit. The results indicate that this visit significantly enhances students' interest in learning and their understanding of the history of Islamic education. Students reported profound spiritual and educational experiences, contributing to their awareness of the importance of Islamic education history within the cultural context of Aceh. Direct interaction with historical sites provides new perspectives, strengthening the connection between the theories learned in class and real-life practices. This research concludes that religious tourism can be an effective method for improving students' understanding of the history of Islamic education. It is hoped that these findings will encourage the integration of religious tourism experiences into the educational curriculum, enriching the learning process and inspiring the development of similar programs in other educational institutions to enhance the quality of education based on local cultural contexts.